Elevated serum prolactin levels as a marker of inflammatory arthritis in psoriasis vulgaris - Hušáková, Markéta; Lippert, Jan; Štolfa, Jiří; Šedová, Liliana; Arenberger, Petr; Lacinová, Zdeňka; Pavelka, Karel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
BACKGROUND AND AIMS: Psoriasis vulgaris (PV) is complicated in up to 40% patients by the inflammatory joint disease psoriatic arthritis (PsA). Neither the aetiology of the arthritis nor specific laboratory markers for its disease activity have been clearly elucidated. Prolactin (PRL) acts as a cytokine with immunomodulatory functions and plays a role in skin and joint biology. The results on PRL however as a marker are unclear. The aim of this study was to confirm whether serum PRL levels reflect systemic complications of PV, like inflammatory joint disease and/or can serve as a marker of disease activity in both cases. METHODS: A total of 70 patients with PV without arthritis and 40 patients suffering from PsA were included. In all patients, we determined skin disease activity according to the PASI index and in PsA, active disease assessed as swollen or tender joints. The control group included 27 age and sex matched healthy individuals. The concentration of PRL in the serum was measured by immunoradiometric assays. RESULTS: The PRL serum levels were significantly increased in PsA patients (299.2±28.29 mIU/L) compared to PV only patients (201.4.2±11.72 mIU/L), P = 0.0003 and healthy individuals (198.2±15.31 mIU/L), P = 0.007. The serum PRL levels in PsA with active disease 336.8±42.50 (mIU/L) were higher than in PV and controls, P < 0.0001 and P = 0.002 respectively. In PV only patients, there was no correlation between PASI and PRL levels. CONCLUSION: Our results showed that PRL serum levels are a marker of active arthritis in PsA and reflects systemic complication rather than local skin activity.
Keywords: Humans; Case-Control Studies; Immunoradiometric Assay; Psoriasis; studie případů a kontrol; Arthritis, Psoriatic; Female; dospělí; psoriáza; imunoradiometrická analýza; lidé; Biomarkers; prolaktin; Adult; Prolactin; biologické markery; ženské pohlaví; Male; psoriatická artritida; mužské pohlaví